Efficiency of mesoporous silica/carboxymethyl β-glucan as a fungicide nano-delivery system for improving chlorothalonil bioactivity and reduce biotoxicity. (January 2022) - Kaziem, Amir E.; Yang, Liupeng; Lin, Yigang; Song, Zixia; Xu, Hanhong; Zhang, Zhixiang
Abstract: Understanding the lethal effects of pesticides nano formulations on the targeted organisms (pathogens) and the non-targeted organisms (fish, earthworms, etc) is essential in assessing the probable impact of new technologies on agriculture and environment. Here we evaluated the bioactivity and the biotoxicity of new type of fungicide smart-delivery formulation based on conjugating carboxymethylated- β -glucans on the mesoporous silica nanoparticles (MSNs) surface after loading chlorothalonil (CHT) fungicide in the MSNs pores. The obtained formulation has been characterized with FE-SEM, and HR-TEM. The CHT loading efficiency has been measured with TGA. The bioactivity of the obtained formulation (CHT@MSNs- β -glucans) has been tested against four pathogens, fusarium head blight ( Fusarium graminearum ), sheath rot ( Sarocladium oryzae ), rice sheath blight ( Rhizoctonia solani ), and soyabean anthracnose ( Colletotrichum truncatum ) compared with CHT WP 75% commercial formulation (CHT-WP) and technical CHT. The environmental biotoxicity of CHT@MSNs- β -glucans compared with CHT-WP has been tested toward earthworm ( Eisenia fetida ) and zebra fish ( Danio rerio ). The results showed that CHT@MSNs- β -glucans has an excellent bioactivity against the subjected pathogens with better inhabiting effects than CHT-WP. CHT@MSNs- β -glucans toxicity to Eisenia fetida was found 2.25 times lower than CHT-WP toxicity. The LC50 of CHT@MSNs- β -glucans to zebra fish after the first 24h was 2.93 times higher than CHT-WP. After 96h of treatment, the LC50 of CHT@MSNs- β -glucans was 2.66 times higher than CHT-WP. This work highlighted the necessity to increase the mandatory bioassays of nano formulations with the major non-target organisms in the environmental risk assessment of new pesticide formulations. Graphical abstract: Image 1 Highlights: In vitro bioassays used to assess toxicity of CHT-WP vs. CHT@MSNs- β -glucans. CHT@MSNs- β -glucans bioactivity against pathogens is better than CHT-WP. CHT@MSNs- β -glucans has lower toxicity to Eisenia fetida than CHT-WP. CHT@MSNs- β -glucans has lower toxicity to zebra fish . CHT@MSNs- β -glucans possessed good biocompatibility and biosafety.